Karen's prize - Martin, Ann M., 1955-; Tang, Susan (New York : Scholastic, 1990)
Karen might be the best junior speller in the state of Connecticut, she is even going to be on TV. Her friends, however, think that she is a show-off.
3.6
3-6
Keywords: Self-perception -- Fiction; Self-perception -- Fiction